1964
DOI: 10.1111/j.1365-2044.1964.tb00365.x
|View full text |Cite
|
Sign up to set email alerts
|

Sterilisation of anaesthetic equipment*

Abstract: During the last few years there have been many publications devoted to almost all aspects of cross-infection. Only a small proportion of these deal with anasthetic equipment and, in particular, little attention has been paid to masks, connecting pieces, corrugated tubing and the other parts of anzesthetic machines. In many hospitals little or no attempt is made to sterilise such equipment. We therefore decided to investigate the question of whether infection is likely to be spread by equipment of this type and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1973
1973
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Its use for disinfection of anaesthetic equipment has been described by Haselhuhn, Wells Brason and Borick (1967) and Meeks, Pembleton and Hench (1967). In both of these studies, contamination was Many of the studies on anaesthetic apparatus reported in the literature have relied on bacteriological swabbing to detect contamination, although a broth sampling method similar to that reported here was used by Jenkins andEdgar (1964), Stratford, Clark andDixson (1964), and Barrow and Meynell (1966). In the present study, swabbing alone would appear to have been ineffective in detecting contamination in a large number of cases.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…Its use for disinfection of anaesthetic equipment has been described by Haselhuhn, Wells Brason and Borick (1967) and Meeks, Pembleton and Hench (1967). In both of these studies, contamination was Many of the studies on anaesthetic apparatus reported in the literature have relied on bacteriological swabbing to detect contamination, although a broth sampling method similar to that reported here was used by Jenkins andEdgar (1964), Stratford, Clark andDixson (1964), and Barrow and Meynell (1966). In the present study, swabbing alone would appear to have been ineffective in detecting contamination in a large number of cases.…”
Section: Resultsmentioning
confidence: 88%
“…DISCUSSION Joseph and Shay (1952) demonstrated high levels of contamination of breathing circuits with streptococci, and Gross (1955) and Rittenbury and Hench (1965) have shown contamination with a variety of pathogenic bacteria. Jenkins and Edgar (1964) showed that pathogens within a patient's respiratory tract readily contaminate anaesthetic equipment, and Henschel, Hollman and Just (1959) showed experimentally that bacteria in anaesthetic tubing could be transmitted to patients during anaesthesia. Shay and Joseph (1952) and Joseph and Shay (1952) have produced evidence which shows that infection may spread from one patient to another as a result of inadequately sterilized anaesthetic tubing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One text advises that PVC tubes may safely be re-used after cleaning and sterilizing (Clutton 1994). Residues such as formaldehyde (Keenleyside 1957), phenolic compounds, (Jenkins & Edgar 1964) and ethylene oxide (Scherer & Holtmann 1986) persisting on ETT have caused tracheitis in people. MedDis (Medichem International, Sevenoaks, Kent, UK) is used in veterinary and human medicine for disinfection of endoscopes and other instruments.…”
Section: Discussionmentioning
confidence: 99%